Formulation and Physical Stability Test of Gel Hand and Body Lotion Methanol Extract of Belimbing Darah Leaves (Baccaurea Angulata) - Deswilyaz, Habibie; Utami, Rury Trisa; Nursaputri, Viona; Gusmali, Desy Maniarti (PT FORMOSA CENDEKIA GLOBAL, 2024)
Antioxidants are chemicals or components that, when present in certain amounts, can prevent or slow down damage caused by the oxidation process. The gel composition has high moisturizing properties due to the high water content. Additionally, it provides a pleasant cooling sensation, making it ideal for use in hot weather conditions. Additionally, it is very good for people with oily skin. The aim of this research was to develop a formulation for an antioxidant gel that includes extracts from blood clot leaves. Baccaurea angulata is blood leaf obtained through a maceration process using methanol as a solvent. Next, the extract is converted into a gel by changing the concentration, which can be 10%, 20%, or 30%. After that, the gel undergoes a physical stability test called Test Cycling, which involves organoleptic tests, homogeneity tests, pH tests, and uniformity tests. The results show that making hand gel and body lotion using methanol leaf extract has excellent physical stability. Among the three different formulations, formula I (10%) is the most superior formulation